CITIZEN EDUCATION KNOWS RESPECT FOR RIGHTS OF HIGH SCHOOL STUDENTS IN BANGKOK - Khammara, Pilailak; Srikolchan, Anchalee (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of this research were: 1) to study the level of citizen education that reflects respect for rights among upper secondary school students in Bangkok, and 2) to explore learning management approaches that promote citizenship characterized by respect for rights. This study employed a mixed methods approach and was conducted in two phases. In the first phase, a survey was administered to 399 upper secondary school students in Bangkok. The sample was selected using stratified random sampling, and the sample size was calculated using Yamane Taro’s formula. Data were collected using a five-point Likert scale questionnaire and analyzed using descriptive statistics: frequency, percentage, mean, and standard deviation. In the second phase, qualitative data were gathered through interviews with key informants to investigate instructional approaches for promoting citizen education with a focus on respect for rights. The data were analyzed using content analysis. The research findings revealed the following: 1) The overall level of citizen education emphasizing respect for rights among upper secondary school students in Bangkok was found to be high. When analyzed by specific dimensions, all aspects were rated at a high level. The highest average score was observed in respect for others’ rights, followed by respect for social rights, while the lowest score was in the dimension of respect for one’s own rights. 2) instructional approaches to promote respect for rights among high school students in Bangkok consist of four components: (1) setting learning outcome goals, including (1) defining learning outcomes, strategies for goal setting, and establishing indicators of learning outcomes; Component 2: Content design; Component 3: Learning activity design; and Component 4: Assessment and evaluation design, which includes four aspects: (1) authentic assessment, (2) reflection and self-assessment, (3) use of diverse assessment tools, and (4) assessment based on potential and continuous development.